2018
DOI: 10.1111/mcn.12703
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a motivational interviewing breastfeeding peer support intervention

Abstract: An uncontrolled study with process evaluation was conducted in three U.K. community maternity sites to establish the feasibility and acceptability of delivering a novel breastfeeding peer-support intervention informed by motivational interviewing (MI;Mam-Kind). Peer-supporters were trained to deliver the Mam-Kind intervention that provided intensive one-to-one peer-support, including (a) antenatal contact, (b) faceto-face contact within 48 hr of birth, (c) proactive (peer-supporter led) alternate day contact f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…Many of our findings in regard to how peer support can influence women’s capabilities, motivation and opportunities for breastfeeding parallel the elements of effective breastfeeding peer support described in the realist review by Trickey et al [29], and in other studies [51] or systematic reviews of breastfeeding support [21]. For example, Trickey et al [29] and the recent multicentre RUBY (Ringing Up about Breastfeeding Early) trial undertaken in Australia found that repeated contacts in the early postnatal period (a risk period for discontinuation), and proactive support, created important opportunities for breastfeeding support [52].…”
Section: Discussionsupporting
confidence: 81%
“…Many of our findings in regard to how peer support can influence women’s capabilities, motivation and opportunities for breastfeeding parallel the elements of effective breastfeeding peer support described in the realist review by Trickey et al [29], and in other studies [51] or systematic reviews of breastfeeding support [21]. For example, Trickey et al [29] and the recent multicentre RUBY (Ringing Up about Breastfeeding Early) trial undertaken in Australia found that repeated contacts in the early postnatal period (a risk period for discontinuation), and proactive support, created important opportunities for breastfeeding support [52].…”
Section: Discussionsupporting
confidence: 81%
“…This juxtaposes to some degree with the ndings of Copeland et al [37], who, in their study, suggest the need for the PSs to maintain the focus of their conversations with mothers upon breastfeeding. Trickey et al [35] found that PSs were more motivated when their work was appreciated, and more responsive to mothers who actively sought their support.…”
Section: Discussionsupporting
confidence: 73%
“…The MITI is recently refined to reflect the developments in the theory of MI and to improve reliability of the measures (MITI 4) (Moyers et al, 2014). The MITI 4 has been applied in some studies so far supporting the reliability to MI and to some extend the validity (Copeland et al, 2019;Moyers et al, 2016;Owens et al, 2017;Serrano, 2018). The MITI 4 provides information on the technical elements of MI by means of a measure of the therapist's ability to cultivate change talk and soften sustain talk; the relational elements empathy and partnership; in addition, detailed information on MI-adherent therapist behavior (affirmation, seeking collaboration, emphasizing autonomy) and MI-non-adherent therapist adherent (confront and persuade) (Moyers et al, 2014) is collected.…”
Section: Instrument To Measure Elements Of MImentioning
confidence: 96%